Urban Art Laboratory as a Form of Engaging with Everyday Life - Nenko, Oleksandra (GSA - Graffiti and Street Art, 2023)
The paper reflects upon my curatorial experience in aninterdisciplinaryurbanart laboratory “The 25 Lines”, which was a 2,5 months collective process takingplace in St. Petersburg on the verge of 2020-20211. The main thesis of the lab was Guy Debord’s statement “Art should return to everyday life” and its main focus was the everydayness of the lines (the streets) of Vasilevsky island. The paper is based on the sociomantic analysis of 40 participants’writtenstatements and 25 artifacts resulting from their engagement with the lines, as well as my personal and my fellow curators’ experiences. In the paper I describe the processuality of the lab, which was built as an intermixture of studies in critical urban theory and performative situated practices, the complexity of this design creating a shared conceptual ground and lived experience space for participants with diverse backgrounds - from performative arts to anthropology. I articulate different research techniques (e.g. drift, dialogue, rhythm analysis, emotional mapping) used by participants to explore the everydayness of the 25 lines and discover their polysemy, human and non-human dynamics, complexity of relations and metaphoricity of their symbolic and material landscapes. I discuss the emergent 25 artifacts, which translated sensual and conceptual experiences of everydayness into a variety of forms - games, installations, artbooks, alternative maps, video-guides, and sculptures. I specifically underline how the emergent artworks broadcasted the direct speech and materiality of the line’s inhabitants’ worlds, places of memory, maps of movements, and other traces of everyday life, otherwise hidden and unrecognized. I summarize by considering the urban art lab as an educational and community-making format linking art, urban studies and everyday lifecriticalreflection,andprovidingspacetoenvision an alternative culture of urban space.